2017
DOI: 10.21511/ppm.15(2-1).2017.10
|View full text |Cite
|
Sign up to set email alerts
|

The influence of trust, communication and commitment on ethical behavior in universities: a case of South Africa

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Studies have shown that the traditional organisational structure hinders effective communication on ABC between departments and other areas of the organisation. For instance, Madwe et al (2020) and Naidoo (2011) suggested that conventional hierarchical structures make it difficult for employees to understand the importance of ABC and its implications for their work.…”
Section: Organisational Structurementioning
confidence: 99%
See 4 more Smart Citations
“…Studies have shown that the traditional organisational structure hinders effective communication on ABC between departments and other areas of the organisation. For instance, Madwe et al (2020) and Naidoo (2011) suggested that conventional hierarchical structures make it difficult for employees to understand the importance of ABC and its implications for their work.…”
Section: Organisational Structurementioning
confidence: 99%
“…Budgetary constraints associated with freezing of fees, government-regulated tuition increases and limited government funding (Aislinn 2015;Su et al 2021) have increased the pressure to reform cost management strategies in state-funded South African universities (Naidoo 2011). The increased competition for limited government funding now means that proper management of escalating costs as well as being cost efficient is imperative in state universities in South Africa.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations